The Capabilities Approaches and Aristotelian Practical Reason - Crespo, Ricardo Fernando (2012)
This paper deals with the problem of how to make decisions about capabilities, as conceived by Amartya Sen. Given their incommensurable character, how to determine the particular set of capabilities to be sought in particular situations? In the last instance I posit that we need a qualitative appraisal, thus introducing the concept of “practical comparability”, which is built on Aristotelian philosophical grounds.